2020
DOI: 10.1111/mcn.12996
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and weight monitoring: A feasibility study of weight charts and midwife support

Abstract: Around half of pregnant women in the United Kingdom are overweight or obese. The antenatal period provides an opportunity for encouraging women to adopt positive lifestyle changes, and in recent years, this has included development of strategies to support women in avoiding excessive gestational weight gain. The objective of this interventional cohort study was to incorporate individualised gestational weight monitoring charts supported by motivational interviewing (MI)‐based conversations into midwifery‐led a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Research has reported on pregnant women’s discomfort discussing weight issues and dislike of regular weight monitoring [ 47 , 48 ]. Moreover, intervention trials in the United Kingdom have reported no effect of routine prenatal weighing or providing women with GWG guidelines [ 49 , 50 ]. Accordingly, sidestepping weight messaging and focusing instead on the more widely motivating message of eating nutritious foods and keeping active to promote maternal and fetal health might be a more effective way of reaching those at greatest risk of excessive GWG.…”
Section: Discussionmentioning
confidence: 99%
“…Research has reported on pregnant women’s discomfort discussing weight issues and dislike of regular weight monitoring [ 47 , 48 ]. Moreover, intervention trials in the United Kingdom have reported no effect of routine prenatal weighing or providing women with GWG guidelines [ 49 , 50 ]. Accordingly, sidestepping weight messaging and focusing instead on the more widely motivating message of eating nutritious foods and keeping active to promote maternal and fetal health might be a more effective way of reaching those at greatest risk of excessive GWG.…”
Section: Discussionmentioning
confidence: 99%
“…We also need to consider that BCTs might operate differently for people with BMIs in different categories; in pregnancy, we know this to be the case in physical activity interventions, 140 but potentially it may also be the case for other BCTs. For example, 'feedback' via self-weighing, which increases the effectiveness of behavioural weight programmes in the general population 155 and is acceptable to women in pregnancy, 156 might be experienced differently by those with a BMI of 25-30 kg/m 2 compared to those with a BMI of > 35 kg/m 2 .…”
Section: Cmo Configuration 5: An Intervention That Is Fit For Purposementioning
confidence: 99%
“…100 As improving the confidence of midwives and obstetrical nurses is crucial to both their success and that of the women and children they care for, many training approaches have been used to teach them novel and practical skills. Education integrated into mandatory training programmes, 68 online training 101,102 and short intensive courses 63 can support midwives and obstetrical nurses by increasing their knowledge of and providing them with opportunities to practise lifestyle promotion interventions such as behaviour change counselling, goal setting and motivational interviewing 103,104 while also learning how to incorporate them into routine practice. 105 Practising new techniques like using open-ended questions, 105 engaging in change talk without giving advice 99 and supporting women to explore and identify their own solutions may be initially challenging for midwives and obstetrical nurses, but it can ultimately be both professionally and personally rewarding.…”
Section: Strategies To Support Midwives and Obstetrical Nurses In Their Rolementioning
confidence: 99%